Intrahippocampal cannabinoid administration induces antinociceptive and amnestic response - Parvin Babaei , and Bahram Soltani Tehrani (Journal of Applied Pharmaceutical Science, 2013)
In the present study, the possible role of a potent cannabinoid agonist, WIN55, 212-2 in the dorsal hippocampus on pain and memory performance has been evaluated. Animals were cannulated in CA1 region of the hippocampus using sterotaxic apparatus. Ten days after recovery, animals were trained in passive avoidance learning (PAL), and immediately received different doses of WIN 55212-2 (0.1, 0.25 and 0.5µg/rat), and were tested 24 h after the training. In the second part of the experiment animals received either WIN 55212-2 (0.5µg/rat) or saline respectively. Tail flick latency was measured three times with 10 minutes interval 30 minutes and 24 hours after the infusion into the CA1. Results indicate that post-training intra-CA1 administration of WIN55, 212-2 (0.25 and 0.5µg/rat) (P< 0.001) reduced step-down latency, showing an amnestic response. Also microinjection of WIN55212-2 (0.5ug/kg) into the CA1 region of the hippocampus induced analgesia compared to control group) (P< 0.01).
Keywords: WIN55, 212-2, Pain, tail flick, cannabinoids, dorsal hippocampus, inhibitory avoidance, rat.